Pemberian Beasiswa Kepada Mahasiswa dengan Metode Preference Selection Index (PSI) - Hutagalung, Juniar; Boy, Ahmad Fitri; Jaya, Hendra; Zulkarnain, Iskandar (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Stikes Santa Elisabeth is an institution in the field of education, especially health. Stikes Santa Elisabeth has many students who come from various regions where many students have difficulty paying tuition due to economic problems. Therefore, many agencies or companies cooperate with Stikes Santa Elisabeth to provide assistance to underprivileged students such as love, single tuition fees (UKT), and the Eka Tjita Foundation. The provision of assistance certainly has rules that must be met by students. Because of the many rules or criteria that must be checked to determine which students will receive assistance, it can often result in the wrong choice as there is a limit to the number of recipients. To overcome these problems, a Decision Support System (DSS) is needed in determining the provision of assistance to students. By applying the PSI method, Stikes Santa Elisabeth can be considered to provide information about the requirements that must be met in receiving assistance. Thus helping Stikes Santa Elisabeth to determine the provision of assistance to students. This study aims to analyze the problems that occur in determining the priority of providing assistance to Stikes Santa Elisabeth students by applying the PSI method based on alternative data and predetermined criteria. Based on the ranking table above, the student who is most prioritized to get a scholarship is Irene Permatasari with a preference selection index value of 0.8765. So it can be concluded that the application of the PSI method results in a ranking so that it can help Stikes Santa Elisabeth to choose students who are the most prioritized in receiving scholarships.